English: English - Ni Putu Dilia Dewi; Dian Rahmani Putri; Ida Ayu Maharani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
The rapid advancement of digitalization presents challenges for English as a Foreign Language (EFL) students in developing speaking skills. The widespread use of online games often leads to passive behavior, limiting opportunities for oral communication practice. In an increasingly competitive world, proficient speaking skills combined with critical thinking are essential for effective communication and problem-solving. To address this gap, the card game